The Christmas Inn : a novel - Kelley, Pamela M. (St. Martin's Griffin, 2024)
"Explore this delightfully cozy and joyful novel of second chances at the most wonderful time of the year, from USA Today bestselling author Pamela Kelley. A feel-good novel as delightful and comforting as a cup of hot chocolate on a cold winter's night, The Christmas Inn is bestselling author Pamela Kelley's most heartwarming and magical book yet. Riley Sanders didn't plan on losing her job as a content marketing manager right before Christmas. When she calls her sister Amy to vent, she learns that their mother has broken her leg and could really use some help at the inn. Riley decides to head home to the inn, nestled along the shores of Cape Cod, in time for the Christmas rush. She is happy to help and needs something to distract her as mistletoe is hung and snowflakes begin to fall. When she gets there, she not only finds delicious cookies and a crackling fire to lift her spirits, but also the sense of family she's been missing all along. There's Franny, a woman who has just lost her sister and has four unopened letters from her that she plans to use to open her up to new experiences on the Cape. And there's Aidan, her high school sweetheart, now a widower, who is staying at the inn with his nine year-old son, Luke. What begins as a quick stay over the holidays to help her mom turns into something that means much more-a second chance at romance, a deeper sense of found family, and all the joy and wonder that comes with Christmastime on Cape Cod"--